The quasi-biennial oscillation: Analysis using ERA-40 data - Pascoe, C; Gray, L; Crooks, SA; Juckes, M; Baldwin, M (2005)
The ERA-40 data set is used to examine the equatorial quasi-biennial oscillation (QBO). The data set extends from the ground to 0.1 hPa (∼65 km) and covers a 44-year period (January 1958 to December 2001), including 18.5 QBO cycles. Analysis of this data set of unprecedented spatial and temporal coverage has revealed a threefold structure in height in the QBO zonal wind anomalies at the equator. In addition to the well-known twofold structure in the lower and middle stratosphere, that is, easterlies overlying westerlies or vice versa, there is a third anomaly in the upper stratosphere. The sign of this upper stratospheric anomaly is the same as the lower stratospheric anomaly, thus forming anomalies of alternating sign throughout the depth of the equatorial stratosphere. The amplitude of this upper stratospheric anomaly is ∼10 m s-1, approximately one third of the amplitude of the lower stratospheric signal. The frequency and descent rates of the east and west QBO phases are analyzed in detail, with particular attention to any 11-year solar cycle influence. In addition to the observed solar modulation of the duration of the QBO west phase the analysis shows a solar modulation of the mean descent rate of the easterly shear zone. The mean time required for the easterly shear zone to descend from 20 to 44 hPa is 2 months less under solar maximum conditions than under solar minimum conditions (7.4 months versus 9.7 months). This rapid descent of the easterly shear zone cuts short the west phase of the QBO in the lower stratosphere during solar maximum periods. Copyright 2005 by the American Geophysical Union.